2019
DOI: 10.1007/s11273-019-09668-1
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem service assessment of selected wetlands of Kolkata and the Indian Gangetic Delta: multi-beneficial systems under differentiated management stress

Abstract: A structured literature review using the search term 'ecosystem services' found few relevant studies relating to three contrasting wetlands in West Bengal: the unpopulated Sudhanyakhali Island in the Sundarbans National Park, the populated Gosaba Island separated from Sudhanyakhali Island by a narrow channel, and the East Kolkata Wetland (EKW). Subsequent structured review focused on the EKW using specific service-related terms located only 2 provisioning, 6 regulating, 1 cultural and 3 supporting services. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…A false name (Alok Halder) is used (for security purposes) in the discussion section to unveil the specific perception of that people or community. Moreover, ESI was adopted separately for each wetland in two different seasons to calculate the spatio-temporal dynamisms of ecosystem services (Everard et al, 2019). Each service has been transformed into numeric score on a scale ranges from 'significantly positive' (++) through 'neutral' (0) to 'significantly negative' (-) and 'unknown' (?)…”
Section: Database and Methodologymentioning
confidence: 99%
“…A false name (Alok Halder) is used (for security purposes) in the discussion section to unveil the specific perception of that people or community. Moreover, ESI was adopted separately for each wetland in two different seasons to calculate the spatio-temporal dynamisms of ecosystem services (Everard et al, 2019). Each service has been transformed into numeric score on a scale ranges from 'significantly positive' (++) through 'neutral' (0) to 'significantly negative' (-) and 'unknown' (?)…”
Section: Database and Methodologymentioning
confidence: 99%
“…Discussions took place primarily in Hindi. Questions were introduced by conversation in locally relevant terms and in a semi-structured way rather than through a rigid questionnaire, reflecting the cultural differences between researchers and local people and the diversity of views of the interviewee group (following Everard et al, 2019). This approach enabled interviewees to respond freely rather than asking them rigorously to stick to precise questions.…”
Section: Key Informant Interviews In Laporiya and Antoli Village Surveysmentioning
confidence: 99%
“…The wetlands serve as a carbon sink with their greenery and water bodies and, in addition, they support purification of the Kolkata's sewage water [103]. In the East Kolkata Wetlands, Everard et al [104] identified a wider diversity of services across all categories of ecosystem services. Among them, water purification and flood regulation significantly serve to secure Kolkata's water security directly.…”
Section: Urban Environmental Water Security Index and Its Spatial Varmentioning
confidence: 99%
“…Among them, water purification and flood regulation significantly serve to secure Kolkata's water security directly. At the same time, provisional ecosystem services in terms of agricultural production (mainly food and flower production) benefit city dwellers in terms of the betterment of the quality of their city lives [104] by providing locally generated products [105]. Mondal et al [102] showed that 14 km 2 of the wetland area of the East Kolkata Wetlands were transformed into urban settlement between 2000 and 2011; due to the vast completion of this process in the first decade of the 21st century, this transformation is not recorded in the study at hand.…”
Section: Urban Environmental Water Security Index and Its Spatial Varmentioning
confidence: 99%